Strategi Kompetitif Berbasis Data: Kajian Literatur Peran Informasi dan Big Data Dalam Menciptakan Diferensiasi dan Inovasi Model Bisnis - Saraswati, Ni Putu Dita; Rizqullah, Radhiansyah; Saragi, Apriyanti; Ayuandini, Risa; Firdaus, Edi (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
The rapid development of the digital economy has shifted the source of competitive advantage from physical assets to the ability of organizations to process data into valuable information and insights. This is crucial because many organizations possess abundant data but are unable to utilize it as a source of strategic value, differentiation, and business model innovation. This study examines the role of Big Data Analytics (BDA) in facilitating the transformation of data into insights that support organizational value creation. The method used is a Systematic Literature Review (SLR) based on PRISMA guidelines for 31 articles from 2020–2025. The results of the study indicate that the value of Big Data does not come from the data itself, but from a structured processing process supported by organizational capabilities such as absorptive capacity, a data-driven culture, knowledge sharing, and strategic agility. These capabilities enable the effective utilization of insights to improve decision quality, market understanding, services, and sustainable business innovation.